Synthesis and Physiological Remodeling of CD34 Cells in the Skin following the Reversal of Fibrosis through Intensive Treatment for Lower Limb Lymphedema: A Case Report - Jose Maria Pereira de Godoy; Ana Carolina Pereira de Godoy; Maria de Fatima Guerreiro Godoy; Dalisio de Santi Neto (MDPI AG, 2023)
A novel type of cell underwent identification between 2005 and 2008 and was denominated the "telocyte" in 2010. In 2012, transmission electron microscopy revealed the presence of telocytes in the dermis. The aim of the present study was to report important changes in immunostained CD34 cells following the treatment of lower limb lymphedema using a specific lymphatic therapy technique. A clinical trial involving the evaluation of changes in immunostained CD34 cells in the epidermis and dermis (10 randomly selected histological fields) of a patient before and after intensive treatment for clinical stage II lymphedema was conducted using the Godoy Method, which was adapted to the treatment of skin fibrosis. The evaluation involved the use of the Weibel multi-point morphometric method. Comparisons were performed using the t-test with a 95% significance level. An important increase in CD34 cells was found with redistribution occurring following treatment. The treatment of primary lymphedema of the lower limbs resulted in the clinical reversal of fibrosis and an increase in the number of immunomarked CD34 cells.